Reproductive hormone profiles and gametogenesis in female of giant gouramy (Osphronemus gouramy) - Wijayanti, Gratiana E.; Soeminto, .; Simanjuntak, Sorta B.I. (Indonesian Society of Scientific Aquaculture (ISSA), 2009)
Giant gouramy is one of freshwater aquaculture fish species that has high economic value so that various efforts had been performed to continuous increase its production levels. The successful of giant gouramy culture requires good understanding on its reproductive biology, however limited information is available. Therefore, this study was conducted to determine reproductive hormone profiles and gametogenesis of giant gouramy for a cycle of reproduction. Eighteen broodstocks were naturally spawned; the day of spawning was referred as the first day (zero weeks) of post spawning. Nine (Group A) of those broodstocks were used to evaluate gonadotropin, estradiol, and progesterone profiles. The remained broodstocks (group B) were used to evaluate gametogenesis. Blood sample from fish group A were taken on 0, 1, 2, 3 and 4 weeks post spawning for measurement of hormone levels. Hormone levels were measured by using ELISA method with kit of REF30-407 for gonadotropin, REF30-431 for estradiol and REF30-406 for progesterone, respectively. On the same time, ovarian were taken from fish group B. Ovarian were weighted to examine gonado somatic index (GSI), and they were then be fixative by NBF solution, processed to histology using paraffin, and stained with haematoxyline-eosin. Histology of ovarian was observed using a light microscope. The results of hormone analysis showed that the level of gonadotropin was relatively high during the spawning (0.17±0.021 mIU/ml), decrease to 0.13±0.017 mIU/ml) at the first week and then relatively stable until the fourth week. Estradiol-17 concentration was relatively high during the spawning (2,222.32±68.19 pg/ml), decrease until the third week and then increase at the fourth week (1,989.66±103.11pg/ml). Progesterone level from fish spawning to the first week was 0.403±0.02ng/ml, increase to 0.514±0.02 ng/ml at the second week and then decrease at the fourth week (0.260±0.0 ng/ml). GSI values from the first week to the fourth were 1.794%; 2.3125%; 2.562% and 4.468%, respectively. Histology analysis showed that giant gouramy has nine oocytes development, including 2 stages of previtellogenesis, 6 stages of vitellogenesis and a post vitellogenesis stage. Information of gonadotropin, estradiol-17 and progesterone profiles, and gametogenesis of giant gouramy could be useful on the effort to optimize their reproductive performance. Keywords: hormone profile, reproduction, gametogenesis, giant gouramy ABSTRAK Ikan gurame merupakan salah satu jenis ikan budidaya air tawar yang memiliki nilai ekonomi cukup tinggi, sehingga berbagai upaya untuk peningkatan produksinya senantiasa dilakukan. Keberhasilan budidaya gurame memerlukan pemahaman yang memadai tentang biologi reproduksi, akan tetapi informasi tersebut masih terbatas. Oleh karena itu dalam penelitan ini dievaluasi profil hormon reproduksi dan gametogenesis gurami selama satu siklus reproduksi. Induk gurame (n= 18) dipijahkan secara alami, hari pada saat ikan memijah ditetapkan sebagai hari pertama (minggu ke-0) pasca mijah. Sembilan ikan (grup A) digunakan untuk evaluasi profil hormon gonadotropin, estradiol dan progesteron. Sembilan ikan lainnya (grup B) digunakan untuk evaluasi profil gametogenesis. Pada minggu ke-0, 1 ,2 ,3 dan ke-4 pasca mijah, sampel darah diambil dari ikan grup A untuk pengukuran kadar hormon. Pengukuran kadar hormon dilakukan menggunakan metoda ELISA dengan kit gonadotropin (REF 30-407), estradil (REF 30-431) dan progesteron (REF 30-406). Pada saat yang sama, ikan dari grup B dimatikan dan dibedah untuk diangkat ovariumnya. Ovarium ditimbang untuk perhitungan gonado somatic index (GSI), kemudian difiksasi dalam larutan NBF, diproses untuk pembuatan sediaan histologi mengguakan metode parafin, dan diwarnai dengan haematoxylin-eosin. Histologi ovari dievaluasi dengan mikroskop cahaya. Hasil pengukuran kadar hormon menunjukkan bahwa kadar godanotropin relatif tinggi pada saat pemijahan (0,17±0,021 mIU/ml) kemudian menurun (0,13±0,017 mIU/ml) pada minggu pertama dan relatif stabil hingga minggu keempat. Kadar estradiol-17 relatif tinggi pada saat pemijahan (2222,32±68,19 pg/ml) menurun hingga minggu ketiga (1518,61±100,68 pg/ml) dan meningkat kembali pada minggu keempat (1989,66±103,11pg/ml). Kadar progesteron pada saat pemjahan hingga minggu pertama 0,403±0,02ng/ml, meningkat menjadi 0,514±0,02 ng/ml pada minggu kedua dan menurun menurun kembali hingga minggu keempat kadarnya 0,260±0,0 ng/ml). Nilai GSI induk betina pada minggu pertama hingga minggu keempat berturut-turut sebesar 1,794%; 2,3125%; 2,562% dan 4,468%. Evaluasi terhadap sediaan histologi ovarium menunjukkan bahwa gurame memiliki sembilan tahapan perkembangan oosit meliputi previtelogenesis (2 tahap), vitelogenesis (6 tahap) dan post vitelogenesis. Informasi tentang profil hormon gonadotropin, estradiol-17 dan progesteron serta profil gametogeness pada gurame dapat digunakan sebagai dasar dalam upaya optimasi reproduksi ikan gurame. Kata kunci: profil hormon, reproduksi, gametogenesis, ikan gurame